2017
DOI: 10.1007/s00277-017-3074-y
|View full text |Cite
|
Sign up to set email alerts
|

D816 mutation of the KIT gene in core binding factor acute myeloid leukemia is associated with poorer prognosis than other KIT gene mutations

Abstract: The clinical impact of KIT mutations in core binding factor acute myeloid leukemia (CBF-AML) is still unclear. In the present study, we analyzed the prognostic significance of each KIT mutation (D816, N822K, and other mutations) in Japanese patients with CBF-AML. We retrospectively analyzed 136 cases of CBF-AML that had gone into complete remission (CR). KIT mutations were found in 61 (45%) of the patients with CBF-AML. D816, N822K, D816 and N822K, and other mutations of the KIT gene were detected in 29 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 31 publications
4
26
1
Order By: Relevance
“…We also provide biologic rationale for the discrepancies in clinical outcomes observed, demonstrating the functional significance of activating E17 abnormalities. The recent study by Yui and colleagues supports our findings demonstrating in adult CBF AML, that only E17 mutations conferred inferior prognosis, with the D816 mutation demonstrating the strongest impact on prognosis (25). Kim and colleagues also reported on the adverse prognostic impact of D816 mutations, which were most pronounced in t(8;21) AML (39).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We also provide biologic rationale for the discrepancies in clinical outcomes observed, demonstrating the functional significance of activating E17 abnormalities. The recent study by Yui and colleagues supports our findings demonstrating in adult CBF AML, that only E17 mutations conferred inferior prognosis, with the D816 mutation demonstrating the strongest impact on prognosis (25). Kim and colleagues also reported on the adverse prognostic impact of D816 mutations, which were most pronounced in t(8;21) AML (39).…”
Section: Discussionsupporting
confidence: 81%
“…Data regarding the prognostic significance of KIT þ CBF AML is conflicting, particularly in children. While some pediatric and dual adult/pediatric studies have failed to show a prognostic impact (2,20,21,23,24), other pediatric series and meta-analyses dispute such findings, suggesting prognostic impact may differ in the context of certain KIT mutations or cytogenetic subgroups (15,17,22,(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that our subjects were exclusively Japanese means that caution is required in the interpretation of the results. In the KIT gene, the N822 mutation has been reported to occur at high frequency in Japanese subjects . We suggest that BCOR mutations may similarly have a high rate of incidence in the Japanese population.…”
Section: Discussionmentioning
confidence: 99%
“…A reflection is that the existence of the KIT mutation brings t(8;21) AML from low to intermediate risk regardless of mutation type in the National Comprehensive Cancer Network guidelines 8 , whereas European LeukemiaNet has provided no further recommendation for those with a KIT mutation 9 . Recently, Yui et al 10 showed that the D816 mutation had a poorer prognosis than other mutations. Thus, it is urgent to perform large-scale studies under modern treatment modes to comprehensively evaluate the prognoses of the individual KIT mutation types.…”
mentioning
confidence: 99%